ANALISIS TANGGUNG JAWAB PENGELOLA PARKIR TERHADAP KEHILANGAN BARANG MAHASISWA UIN JAKARTA - Rizqi Rahma Adinda; Muhammad Haikal (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the responsibility of parking managers for the loss of goods in parking areas considering that the increasing number of motorized vehicles in Indonesia creates additional problems in the required parking management system. Parking managers are responsible for the security of vehicles and goods in the parking area based on Article 1706 and Article 1714 of the Civil Code (KUHPerdata). Parking management is a matter of public law, but if a relationship exists between the parking manager and consumers, then the concept of certainty and the existence of rights and obligations will give rise to concepts in private law. In 2019, the National Consumer Protection Agency (BPKN) issued Circular Number 1 of 2019 concerning Consumer Protection regarding the Responsibilities of Parking Managers which emphasized that parking managers are responsible for lost goods that occur in the parking area. The parking manager can be held liable by the injured party on the basis of a breach of contract (negligence) in the goods custody agreement between the parking lot manager and the motorbike owner. In the case of lost items from UIN Jakarta students, the parking lot manager can be held responsible for the losses experienced by the student. Parking lot managers also have a moral responsibility to maintain the safety of goods entrusted to them by consumers. Efforts such as strict supervision, installing CCTV cameras, and providing experienced and trained parking attendants must be taken to prevent loss of goods from consumers.